Menyelisik Keberadaan Seni Kriya Keris Pusaka pada Era Globalisasi (Studi Kasus Perajin Keris di Desa Aeng Tong-Tong Kecamatan Seronggi Kabupaten Sumenep Madura) - Wulandari, Nur Laila; Suarsana, I Nyoman; Murniasih, A.A. Ayu (Sunari Penjor : Journal of Anthropology; Vol 6 No 1 (2022), 2022)
Research on the Existence of Heirloom Keris in the Era of Globalization (Case Study of Keris Craftsmen in Aeng Tong-Tong Village, Sumenep Madura) originated in the global era, keris is seen as an object that has its own elements and advantages.  This study tries to examine the existence of heirloom kerises in the current era of globalization which is starting to develop.  The main problem in this research is focused on the existence of heirloom kerises in Aeng Tong-Tong Village in the era of globalization.  The theory used in this study uses the theory of symbolic interactionism and the theory of functionalism.  The approach used is a qualitative approach with the type of descriptive-qualitative research.  Data collection techniques used are observation, interviews, documentation, and literature studies.  The results of the study reveal that the kris as a cultural artifact, in the development of the era of globalization, is faced with two choices.  First, the conservation view requires that all cultural forces are always oriented to the past, so they must maintain the core values ??of that culture.  Second, the progressive view requires changes that lead to cultural modernization.